Analysis of Technical Guidance Implementation: Evaluation of Voting and Vote Counting by KPPS in the 2024 Election in North Petukangan - Jatmiko Putri, Khansa Khairun Nisa; Khaila, Ananda Putri; Firmansyah, Fadly; Nainggolan, Dina Thalentaria; Azmy, Ana Sabhana (Kybernology : Journal of Government Studies, 2024)
Elections are a characteristic of a democratic country, held once every 5 years in Indonesia. The holding of democratic elections can’t be separated from the democratic implementation process. Since 2015, elections have been held simultaneously. The 2024 elections will include legislative and presidential votes. In the 2024 elections, several problems have arisen due to the limited number and experience of PPS members, the "technical guidance" implementation schedule, the mechanism for implementing "technical guidance" materials, ad hoc recruitment process, the professionalism and heavy workload of KPPS . Based on these issues, this research aims to analyze the ability to implement technical guidance materials during the voting and vote-counting process by KPPS in the 2024 elections, focusing on the North Petukangan Subdistrict, Pesanggrahan District, South Jakarta. This study used qualitative research methods. Data collection was carried out through interviews in the field with relevant stakeholders. The results of the research indicate that there are still significant obstacles in implementing the voting and vote-counting process by KPPS in North Petukangan Subdistrict. This is influenced by various factors, such as limited time and space in distributing "technical guidance" materials, technological obstacles related to Sirekap, as well as the limited knowledge and experience of KPPS members.